SYSTEMATIC REVIEW OF PHYSICAL ACTIVITY AND SEDENTARY BEHAVIOR INDICATORS IN SOUTH-AMERICAN PRESCHOOL CHILDREN - Paulo Henrique Guerra; Valter Cordeiro Barbosa Filho; Angélica Almeida; Letícia de Souza Silva; Marcelo Tedesco Vidal Pinto; Renan Martinelli Leonel; Evelyn Helena Corgosinho Ribeiro; Alex Antonio Florindo (Sociedade de Pediatria de São Paulo, 2019)
ABSTRACT Objective: To summarize indicators and describe in detail the methods used to physical activity and sedentary behavior measurement in South American preschool children. Data source: In 2017, we searched for articles on researches carried out in South American countries, which presented physical activity and/or sedentary behavior indicators in children aged two to six years. These searches were conducted in Spanish, English, and Portuguese in four electronic databases (LILACS, PubMed, SciELO, and Web of Science), Google Scholar, and in reference lists. Data summary: Out of 416 articles initially assessed, 13 composed the descriptive summary. Samples from Argentina, Brazil, and Chile were included. Three articles provided accelerometer-based estimates of moderate physical activity: 32, 70.1, and 71.3 minutes per day. The mean total sedentary behavior was 468.3 and 562.9 minutes per day and, considering the cut-off point of 2 hours per day of screen time, we found the following prevalence rates: 39.4, 40.3, and 100%. The studies adopted a wide number of instruments and strategies to evaluate those behaviors. Conclusions: Although the summary has pointed to high exposure to sedentary behavior in preschool children, with particular focus on screen time, it is essential to broaden the discussion and approximate the methods used to assess physical activity and sedentary behavior, making the evidence more comparable and strong, so as to elaborate preventive strategies and actions.